2019
DOI: 10.1590/s0100-83582019370100085
|View full text |Cite
|
Sign up to set email alerts
|

Interference of Brassicaceae and Poaceae on Canola Hybrids

Abstract: The objective of this study was to evaluate the initial competitive ability of canola hybrids against Brassicaceae and Poaceae species in terms of root and shoot resources. Two experiments were conducted in greenhouse, in a completely randomized design with four replications. The treatments consisted of interference conditions by root + shoot interference (root+shoot) and shoot interference (Light); and Brassicaceae and Poaceae weeds competing with hybrid of canola (Hyola 61 and Diamond) with different traits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In competitive studies with ryegrass (Lolium multiflorum), which is also a Poaceae, the behavior between canola varieties determined the survival strategy generated by the competition (34); for example, the hybrid Hyola 571 invests in taller plants, allowing greater capture of solar radiation (22). In this study, the difference in architecture between species showed greater differentials, where the canola was more efficient in capturing light when compared to some Poaceae species (33,36).…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…In competitive studies with ryegrass (Lolium multiflorum), which is also a Poaceae, the behavior between canola varieties determined the survival strategy generated by the competition (34); for example, the hybrid Hyola 571 invests in taller plants, allowing greater capture of solar radiation (22). In this study, the difference in architecture between species showed greater differentials, where the canola was more efficient in capturing light when compared to some Poaceae species (33,36).…”
Section: Resultsmentioning
confidence: 70%
“…The mass accumulation of canola was consistent with the final grain production (20); thus, any weed species interference will result in loss of yield. With the development of more competitive hybrids, it has been possible to use more aggressive species, obtaining a higher final grain yield in the presence of weeds compared to less competitive hybrids (33). In field conditions, the use of more competitive hybrids can decrease up to 50% of the accumulation of biomass in weeds (21).…”
Section: Resultsmentioning
confidence: 99%